Use of Video Laryngoscope during Intubation in Patients with Non Difficult Airway - Acharya, Sulav; Khanal, Anupa; Yadav, Rajiv; Baral, Sushil (Nepal Medical College Journal, 2024)
Endotracheal intubation using laryngoscope which is an important skill required for all anesthesiologist in day to day practice is considered as gold standard for airway management. Various methods can be used for endotracheal intubation of which direct laryngoscopy is most commonly used and video laryngoscopy is an alternative. The success rate of tracheal intubation in cases of difficult airways has increased dramatically with the use of video laryngoscopes and improvements in the degree of glottic exposure. Hence this study aims to evaluate the laryngoscopic view, ease of intubation and haemodynamic changes during intubation using video laryngoscope in patients with non difficult airway. This interventional study was conducted in fifty nine patients of ASA I or II, ≥18 yrs of age with Mallampati grade I or II, mouth opening >3 cms, thyromental distance >6.5 cms of either sex planned for elective surgery under general anesthesia. General anesthesia was induced with similar doses for all the patients and intubated using video laryngoscope. Cormack-Lehane grade, intubation time, number of attempts for intubation and haemodynamic parameters were recorded. In this study, all patients had grade I type of laryngeal view during laryngoscopy and the mean time required for intubation was 18.93±7.08 sec. Out of 59 patients, 58 (98.3%) were intubated in single attempt and there was no significant haemodynamic changes during laryngoscopy with video laryngoscope. Hence, the result of this study concluded that endotracheal intubation using video laryngoscope provides good laryngoscopic view, better intubating condition for the ease of intubation without significant haemodynamic changes, thus considering worth for intubation of non difficult airway.